Authority To Determine A Person To Become A Justice Collaborator In The Criminal Justice Process - Dani - Durahman; Fangky Christina Indraguna (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
The Investigation is the initial series of the criminal justice process. In practice, the examination process requires witness statements in finding a bright spot in the case. Justice collaborators are a means to facilitate investigators in uncovering cases. Technically, protection in the form of awards for justice collaborators is carried out in accordance with the provisions of the Joint Regulations. Applications are submitted by the perpetrators themselves to the Attorney General. Furthermore, in the event that the Attorney General grants the request for an award, the Public Prosecutor must state in his lawsuit the role played by the justice collaborator in assisting the law enforcement process so that it can be considered by the judge in making a decision. The purpose of this study resulted in the determination of investigators who have the authority to determine the Justice collaborator. Results of the study The presence of a justice collaborator in disclosing a case, especially one that is organized crime is urgently needed considering that its role is very central and urgent. The cooperation of justice collaborators with law enforcement officials can facilitate the task of disclosing a crime, especially those related to the public interest (openbare order) or the state. The logical consequence is that one of the instruments that can be used to encourage disclosure or reporting of a crime is by providing guarantees and protection to justice collaborators because without this role it is very difficult to disclose organized crime, usually these difficulties arise due to weak support. evidence/evidence obtained due to the limitations of law enforcement officials in obtaining evidence that is significant enough to reveal the crime. Problematic and overlapping aspects of who can determine a person to become a justice collaborator, whether the LPSK, Investigator, Prosecutor, or Judge. In order to create legal certainty, the authority to determine someone to become a justice collaborator is the authority of the investigator as the first institution to carry out legal proceedings.